Lower Cretaceous bryozoans from Argentina: a 'by-catch' fauna from the Agrio Formation (Neuquén Basin) - Taylor, Paul D. (2009)
Mesozoic bryozoans are uncommon in the Southern Hemisphere and none have yet been described from the Lower Cretaceous of Argentina. This paper describes six taxa from the lower Valanginian to the upper Hauterivian-?lower Barremian Agrio Formation of the Neuquén Basin. New species are Charixa burdonaria sp. nov., notable for being the oldest known spine-bearing cheilostome and for constructing multilayered colonies intergrown with serpulid worms, and an unusual cyclostome described as Neuquenopora carrerai gen. et sp. nov. The poor preservation and/or lack of diagnostic gonozooids makes taxonomic assignment of the remaining bryozoans, all cyclostomes, uncertain. Apart from Multizonopora sp., a cerioporine cyclostome with bushy, ramose colonies, all of the Agrio Formation bryozoans are encrusters. In general, the Agrio Formation bryozoan fauna resembles faunas from the Neocomian and Aptian of north-west Europe. The relatively low diversity may be an artefact of collecting effort, although environmental factors may also be important, with the intergrowths between C. burdonaria and serpulids from the top of the Agrio Formation being reminiscent of some present day occurrences of primitive cheilostomes in lagoons with fluctuating salinities.